A 'Pretensed and Counterfeit Holiness' or Sowers of 'Spiritual Things'? John Jewel and Thomas Harding on Monasticism. Issue 1 (May 2016) - Peters, Greg
Though Bishop John Jewel did not say much against the institution of monasticism in his Apologia Ecclesiae Anglicanae, he does have much to say about it in his other works. An examination of his opinions on monasticism show that he is in general agreement with other Reformation-era views of monasticism, including some Anglican divines as well as Martin Luther, John Calvin and Ulrich Zwingli. The Roman Catholic Thomas Harding's A confutation of a booke intituled An apologie of the Church of England took Jewel to task for his misunderstanding of monasticism. Jewel, in due course, responded to Harding in his A defence of the Apologie of the Churche of Englande by stitching together a litany of quotations from the early and medieval Church to show that Harding was mistaken. Though Jewel's rhetorical strategy in this instance has been called a 'polemical duplicity' by Gary Jenkins, it is part of Jewel's larger rhetorical strategy. This article investigates the writings of Jewel to discern his understanding of monasticism, showing that Jewel's rejection of monasticism falls under the principle of abusus tollit usum ('abuse removes use'), whereas Harding's response conforms to traditional Catholic Reformation understandings of the monastic life. An analysis of Jewel's litany of patristic and medieval sources that supposedly oppose monasticism shows how he often misuses his sources. At all times due consideration is given to both Jewel's and Harding's rhetorical strategies in their disagreement. In the end, Jewel's views of monasticism, though in agreement with many other Reformers, are not wholly consistent with 16th-century views of monasticism in England.